1985
DOI: 10.1016/0035-9203(85)90323-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus circulation in three different villages of Somalia

Abstract: Hepatitis B virus (HBV) circulation was surveyed in three Somalian villages (Buur-Fuul, Mooda-Moode and Bajuni Islands) in different districts and 52 children living in a closed community, aged under one year, were studied. Of the 331 village subjects aged one to 83 years, 12.08% were HBs positive, 29.9% anti-HBs positive, 43.8% anti-HBc positive and 21.4 anti-HBe positive. Among the HBs-positive subjects, 34.7% had HBeAg and 21.7% had anti-HBcAg-IgM. No statistically significant differences were found for HBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Similar to other African countries [Greenfield et al, 1986;Windsor et al, 1984;Said et al, 1985;Gebreselassie, 1984;Coursaget et al, 1984;Ahmed et al, 1984;Werner et al, 1985;Sebastiani et al, 1985;Sherif, 1985;Khalfa and Ardjoun, 1984;Henriksen, 1984;Bowry, 1983;Prozesky et al, 1983;Gebreselassie, 1983a;Bowry, 19831 prevalence of hepatitis B markers is high among Ethiopians: by the age of 20 over 70% of the healthy young men are already positive to at least one marker, indicating that most of the infections occur at an earlier age. This feature of a common infection occurring early in life explains the high rate of liver cirrhosis and primary liver carcinoma observed in Ethiopia [Health Manpower Study: "Ethiopia"; The Ministry of Health, Addis Ababa Ethiopia, 1980; Lester and Tsega, 19761.…”
Section: Discussionmentioning
confidence: 80%
“…Similar to other African countries [Greenfield et al, 1986;Windsor et al, 1984;Said et al, 1985;Gebreselassie, 1984;Coursaget et al, 1984;Ahmed et al, 1984;Werner et al, 1985;Sebastiani et al, 1985;Sherif, 1985;Khalfa and Ardjoun, 1984;Henriksen, 1984;Bowry, 1983;Prozesky et al, 1983;Gebreselassie, 1983a;Bowry, 19831 prevalence of hepatitis B markers is high among Ethiopians: by the age of 20 over 70% of the healthy young men are already positive to at least one marker, indicating that most of the infections occur at an earlier age. This feature of a common infection occurring early in life explains the high rate of liver cirrhosis and primary liver carcinoma observed in Ethiopia [Health Manpower Study: "Ethiopia"; The Ministry of Health, Addis Ababa Ethiopia, 1980; Lester and Tsega, 19761.…”
Section: Discussionmentioning
confidence: 80%
“…In 1985, a study conducted in three different villages of Somalia found that 12.08% (40/331) of subjects aged 1-83 years were HBsAg-positive, 29.9% were anti-HBs-positive, 43.8% were anti-HBc-positive, 21.4% were anti-HBe-positive, and the overall prevalence in this study was 12% (46/383) of subjects, including those under one year of age. Among the HBsAg-positive subjects, 34.7% were HBeAg-positive and 21.7% had anti-HBcAg-IgM[ 27 ]. A survey study in 1987 of HBV epidemiology was carried out among 383 adults from different areas of Somalia and in 135 pregnant women and 428 children from Mogadishu.…”
Section: Resultsmentioning
confidence: 99%
“…A total of six studies showed HBV prevalence rates between 0% to 16% among children[ 16 , 27 - 30 , 40 ]. See Table 5 .…”
Section: Resultsmentioning
confidence: 99%
“…High prevalence of HBV infection was reported from various parts of Africa among different population groups [4][5][6][7][8][9][10][11][12][13]. Although there were some reports on the prevalence of HBV in Somalia in the past [14][15][16][17][18] there is limited recent literature on the prevalence of HBV infection in Somalia. The country is among the endemic areas with high prevalence of HBV infection [19].…”
Section: Introductionmentioning
confidence: 99%